Optimalisasi Pengabdian Kepada Masyarakat di wilayah Banjarbaru sebagai Upaya Meningkatkan Kesadaran Deteksi Dini Penyakit - Okta Muthia Sari; Putri Helena Junjung Buih; Nanda Hesti Rahmawati; Siti Najwa; Firdarima Salsabila; Indah Maharati Zoan; Luthfia Azzahra; Syahrul Yaiis Abdul Rahman (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Ichsan Gorontalo, 2026)
Low public awareness regarding routine health monitoring remains one of the major contributing factors to the increasing prevalence of non-communicable diseases such as hypertension, diabetes, and metabolic disorders. This condition is evident among the community of Gunung Ulin Village and the Sunday Morning Paguyaga Mitra Praja area in Banjarbaru, where most individuals are informal workers, vendors, and visitors with limited time and access to health services. This community service program aimed to improve health awareness and understanding through free health screening including blood pressure, blood glucose, uric acid, and cholesterol accompanied by consultation and education regarding the interpretation of results. The program was conducted on May 18 and 28, 2025, involving lecturers and students as facilitators. A total of 84 participants took part in the activity, with findings showing that most participants had elevated blood pressure, while the results for glucose, uric acid, and cholesterol varied according to individual health histories. The educational component increased participants’ understanding of their health status and encouraged preventive actions. Overall, the program was effective in enhancing health literacy, early detection awareness, and healthy behavior within the community. Future programs are expected to be conducted in more conducive locations to optimize service quality and participant comfort.